0001 Keeping older adults independent: it takes a village. (26th April 2015) - Moss, Harrison; Bauer, Michael
Abstract : Statement of purpose: Falls among older New Yorkers are the leading cause of injury deaths, hospitalizations, and emergency department visits. Fall injuries among older New Yorkers result in over $2.3 billion in hospital and emergency department charges every year. Those who fall often suffer a downward spiral in physical and mental health, ultimately taking away an individual's independence. Methods/Approach: The NYS Older Adult Fall Prevention Program supports evidence-based programs in three counties. The evidence-based community programs include Tai Chi for Arthritis, Tai Chi: Moving for Better Balance, and Stepping On . An innovative approach has been using the STEADI Toolkit to integrate fall prevention assessment and referral into clinical practice. STEADI (Stopping Elderly Accidents, Deaths, and Injuries) provides primary care providers the tools to assess older adult patients for fall risk and then refer them to evidence-based community programs and resources. The state health department partnered with a variety of state, county, and local organisations to facilitate program implementation and sustainability. Results: These programs improve quality of life, preserve independence, and reduce health care costs. These programs have reached nearly 1, 500 older New Yorkers. At a healthcare system based in Broome County, over 170 physicians across 17 practices spanning four counties now utilise the STEADI Toolkit to conduct fall risk assessments and referrals. Such assessments and referrals are tracked via modified electronic health records. Conclusions: Evidence-based fall prevention programs can be delivered through a variety of community partners. Referring older adults into these programs via fall risk assessment in the primary care setting enhances program reach. Significance and contribution to the field: Implementing evidence-based fall prevention programs in community and healthcare settings through state health departments is an effective public health strategy to reach community-dwelling older adults.